Years of potential life lost amongst heroin users in the Australian Treatment Outcome Study cohort, 2001–2015. (1st May 2016) - Darke, Shane; Marel, Christina; Mills, Katherine L.; Ross, Joanne; Slade, Tim; Tessson, Maree
Highlights: Mortality rates of the Australian Treatment Outcome Study (ATOS) cohort at 2015, and years of potential life lost (YPLL), were calculated. 11.7% were deceased, with a crude mortality rate of 9.2 per 1000 PYs. The standardised mortality ratio was 10.2 (males 7.3, females 17.2). Mean YPLL was 27.6 (CDC criterion), and 43.5 below average life expectancy. Overdose and suicide accounted for 75.8% of YPLL. Abstract: Background: Heroin use carries the highest burden of disease of any drug of dependence. The study aimed to determine mortality rates of the Australian Treatment Outcome Study cohort over the period 2001–2015, and the years of potential life lost (YPLL). Methods: The cohort consisted of 615 heroin users. Crude mortality rates per 1000 person years (PY) and Standardised Mortality Ratios (SMR) were calculated. YPLL were calculated using two criteria: years lost prior to age 65, and years lost prior to average life expectancy. Results: The cohort was followed for 7, 790.9 PY. At 2015, 72 (11.7%) of the cohort were deceased, with a crude mortality rate of 9.2 per 1000 PYs. Neither age nor gender associated with mortality. The SMR was 10.2 (males 7.3, females 17.2), matched for age, gender and year of death. The most common mortality cause was opioid overdose (52.8%). Using the <65 years criterion, there were 1988.3 YPLL, with a mean of 27.6 (males 27.6, females 27.7). Using the average life expectancy criterion, there were 3135.1 YPLL, with a mean of 43.5 (males 41.9, females 46.3). Accidental overdose (<65yr 63.0%, average life expectancy 63.7%) and suicide (<65yr 12.8%, average life expectancy 13.3%) accounted for three quarters of YPLL where cause of death was known. Conclusions: YPLL associated with heroin use was a quarter of a century, or close to half a century, depending on the criteria used. Given the prominent role of overdose and suicide, the majority of these fatalities, and the associated YPLL, appear preventable.